Integrating Uzbekistan’s Cultural Heritage Into Modern Education: National Identity And Global Harmony (Jadidism) (Zien Journal of Social Sciences and Humanities, 2025)
This article explores the integration of Uzbekistan’s cultural heritage into modern education through the lens of Jadidism as a historical, intellectual, and pedagogical movement. Jadidism, which emerged in the late 19th and early 20th centuries, played a crucial role in shaping national identity by harmonizing Islamic values, modern science, and progressive educational reforms. The study analyzes how Jadid ideas—such as educational modernization, cultural renewal, and social reform—can be reinterpreted and applied within contemporary educational systems. Special attention is paid to the balance between preserving national identity and engaging with global educational standards. By employing a multidisciplinary approach that combines historical analysis, educational theory, and cultural studies, the article demonstrates that Jadidism offers a valuable conceptual framework for integrating cultural heritage into modern curricula. The findings suggest that incorporating Jadid intellectual heritage into education fosters cultural continuity, critical thinking, and global awareness, thereby contributing to the formation of a socially responsible and culturally grounded generation